The Relationship Between Ward Head Supervision and Nurse Performance in Nursing Care Documentation: a Cross-Sectional Study - Langingi, Ake Royke Calvin; Rembet, Ignatia Yohana; Watak, Chintami Luciana; Pagayang, Zefania Ireyne; Rasu, Stella (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the relationship between head nurse supervision and nurse performance in documenting nursing care. Using a cross-sectional design, the research involved 120 nurses selected through total sampling. Data analysis included univariate and bivariate methods, yielding a p-value of 0.000 and an OR of 5.538, indicating a significant relationship between supervision and nurse performance. The findings highlight the importance of effective supervision in improving nursing care documentation at Gunung Maria Tomohon General Hospital. This study recommends utilizing the results as educational material for nursing students to enhance their knowledge of nursing care practices.